The Effect of Interactive Snakes and Ladders Game on Improving Elementary School Students' Basic Motor Skills - Siti Mutamimah; Himly Aliriad; Rohmad Apriyanto (Jurnal Elementaria Edukasia, 2026)
Fundamental movement skills are an essential foundation for the motor development of elementary school students, particularly in lower grades where children experience rapid motor growth. However, physical education learning in elementary schools is often dominated by conventional teaching methods that provide limited opportunities for active student engagement. The use of interactive digital game-based learning media is considered a potential strategy to enhance students’ motor stimulation and learning involvement. This study aimed to examine the effect of an audio-visual interactive snakes and ladders game on improving fundamental movement skills of elementary school students. The research employed a pre-experimental method using a one group pretest–posttest design. The population consisted of all second-grade students at UPT SDN Kemlaten, with a total sample of 18 students selected through total sampling. Data were collected using an observation checklist assessing five aspects of fundamental movement skills: balance, coordination, locomotor skills, non-locomotor skills, and manipulative skills. Data analysis was conducted using normality tests and a paired sample t-test. The results indicated a significant difference between pretest and posttest scores with a significance value of < 0.05, demonstrating an improvement in students’ fundamental movement skills after the implementation of the interactive learning media. In conclusion, the audio-visual interactive snakes and ladders game is effective in enhancing fundamental movement skills of lower-grade elementary school students and can serve as an innovative and engaging alternative learning medium in physical education classes.